MY CART (5)
ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price:

There are no items in this cart.
Continue Shopping
                   

If m= sin6x + cos6x, then m belongs to the interval


(a) [7/8, 5/4]  (b) [1/2 , 5/8]  (c) [1/4,  1]


Explain pls...

3 years ago

Share

Answers : (1)

                                        

m=sin6x+cos6x=(sin2x+cos2x)(sin4x+cos4x-sin2xcos2x)


as a3+b3=(a+b)(a2-ab+b2)


we know that,


sin2x+cos2x=1


m=((sin2x+cos2x)2-3sin2xcos2x)


m=1-3sin2xcos2x


m=1-3/4(sin2x)2


we know 0<=sin2A<=1,


so -1<=-sin22x<=0 multiply with -1,


-3/4<=-3/4(sin22x)<=0 multiply with 3/4,


1/4<=1-3/4(sin22x)<=1 add 1,


1/4<=m<=1


therefore "m" belongs to[1,1/4].

3 years ago

Post Your Answer

More Questions On Trigonometry

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
If sinx+siny=root3(cosy-cosx) Prove that sin3x+sin3y=0.
 
 
Hello students, please check the solution of your question given below: sinx+siny = root3 ( cosx-cosy) 2sin(x+y/2)cos(x-y/2) = root3 {2sin(x+y/2)sin(y-x/2)} sin(x+y/2)[cos(x-y/2)-root3....
  img
Sunil Raikwar 6 months ago
 
Dear student, According to the given relation, we would have: If we multiply both sides by a factor of 4, we get: This on simplifying gives us: If the right hand side can be simplified to...
  img
Sumit Majumdar 6 months ago
( * ) 1 – (sin square y) / (1+cos y) + (1 + cos y) / ( sin y) – (sin y) /(1-cos y) =
 
 
Hello student, Please find the answer to your question below 1 – (sin square y) / (1+cos y) + (1 + cos y) / ( sin y) – (sin y) /(1-cos y) = cos 2 y / (1 + cosy ) + (1 + cos y) /...
  img
Nishant Vora 5 months ago
( * ) If cos theta – 4 sin theta = 1, then sin theta + 4 cos theta =
 
 
Hello student, Please find the answer to your question below cos theta – 4 sin theta = 1 …....(1) sin theta + 4 cos theta = k….…..(2) Square and add both the...
  img
Nishant Vora 5 months ago
prove that n 3 + 3n 2 + 5n + 3 is divisible by 3 for any natural number n
 
 
Hello Student, n^3 + 3n^2 + 5n + 3 =n^3 + 3n^2 + 2n+3n + 3 =n(n^2 + 3n + 2)+3n + 3 =n(n+1)(n+2)+3n+3 Prooved Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 7 months ago
 
By Fermat’s theorem, n 3 -n is divisible by 3. Hence n 3 +3n 2 +5n+3 = (n 3 -n)+(3n 2 +6n+3) = 3m+3(n+1) 2 for some integer m making the expression obviously a multiple of 3.
 
mycroft holmes 7 months ago
At what values of 'a' do all the zeroes of the function, f(x) = (a-2)x 2 + 2ax + a + 3 lie on the interval (-2, 1)?
 
 
Hi, You need to consider 2 cases here. Case 1 : Take a-2>0 Now the concavity is upwards, draw the desired graph and think about the conditions. We need f(-2)>0 f(1)>0 \ But this is...
  img
Yash Baheti 5 months ago
 
The answer includes {2} . But leading coeff. is not equal to 0. Am i right ???
 
piyush soni 5 months ago
please explain fully …...please …...hey image attached please tell the method which is used in solution …..please sir .maam …..please anyone …...
 
 
Ans: Hello student, Please find the answer to your question below [] is greatest integer function. [t] = 0, 0 <=t < 1 [t] = 1, 1 <= t < 2 Now looking at the problem in hand There...
  img
Jitender Singh 5 months ago
View all Questions »